Harmony Between Building Use Rights (HGB) Regulations and Defense Policies: A Customary Law Perspective in Natural Resource Management - Dedy Muharman (Journal of Adat Recht, 2025)
This study examines the harmony between the regulation of Building Use Rights (HGB), defense policies, and customary law in natural resource management in Indonesia. The disharmony among these three aspects often leads to land conflicts, resulting in legal uncertainty for indigenous communities. HGB regulations and defense policies tend to prioritize the interests of right holders and national defense, while legal recognition of indigenous land rights (ulayat rights) remains limited. As a result, indigenous communities lose access to land and natural resources that are integral to their economic, social, and cultural life. This study employs a normative juridical method with legislative, conceptual, and case approaches to identify regulatory disharmony and its impact on indigenous communities. The findings reveal that land conflict resolution often favors HGB holders and defense policies, with minimal involvement of indigenous communities in decision-making processes. Therefore, a more inclusive land policy is needed by strengthening the recognition of ulayat rights, integrating customary law into national regulations, and developing effective land dispute mediation mechanisms. This regulatory harmonization is expected to create a balance between state interests, right holders, and indigenous communities in sustainable and equitable natural resource management.